2017
DOI: 10.1111/afe.12241
|View full text |Cite
|
Sign up to set email alerts
|

Genetics‐based methods for agricultural insect pest management

Abstract: The sterile insect technique is an area‐wide pest control method that reduces agricultural pest populations by releasing mass‐reared sterile insects, which then compete for mates with wild insects. Contemporary genetics‐based technologies use insects that are homozygous for a repressible dominant lethal genetic construct rather than being sterilized by irradiation.Engineered strains of agricultural pest species, including moths such as the diamondback moth Plutella xylostella and fruit flies such as the Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…Second, males heterozygous for the male-selecting allele can survive to maturity and potentially confer the allele upon their own offspring. This further reduces the future reproductive potential of the population, introgressing alleles for insecticide susceptibility and increasing the efficacy of a subsequent insecticide application (Alphey et al 2007, Harvey-Samuel et al 2015, Leftwich et al 2016, Alphey and Bonsall 2017, Zhou et al 2018. By, at least partially, recognizing these benefits, look-ahead policies were able to incorporate releases into their action sequences, reducing their dependency upon insecticide, an ecologically desirable outcome given the controversy surrounding pesticides and the environmental consequences of their overuse (Guedes et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, males heterozygous for the male-selecting allele can survive to maturity and potentially confer the allele upon their own offspring. This further reduces the future reproductive potential of the population, introgressing alleles for insecticide susceptibility and increasing the efficacy of a subsequent insecticide application (Alphey et al 2007, Harvey-Samuel et al 2015, Leftwich et al 2016, Alphey and Bonsall 2017, Zhou et al 2018. By, at least partially, recognizing these benefits, look-ahead policies were able to incorporate releases into their action sequences, reducing their dependency upon insecticide, an ecologically desirable outcome given the controversy surrounding pesticides and the environmental consequences of their overuse (Guedes et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sterile insect releases can complement insecticidal sprays to achieve greater overall levels of suppression than when either control is used in isolation: in general, sprays are most effective when employed against a large population while the efficiency of sterile releases can increase as the target population declines (Barclay 2005). However, there has been a diversification of sterile insect methods in recent years, driven by developments in genetic engineering, resulting in novel approaches such as gene-drive systems, male-selecting strains, and sex ratio distortion (Bourtzis et al 2016, Leftwich et al 2016, Alphey and Bonsall 2017, Harvey-Samuel et al 2017. Male-selecting strains are of particular relevance to resistance management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CRISPR-mediated transgenic introduction of dominant conditional lethal mutations that specifically target females would facilitate production of genetic sexing strains, which has been proven to dramatically improve the efficiency and economics of SIT with the medfly, Ceratitis capitata (Wiedemann). Additionally, utilization of repressible dominant lethal genes that are present in males, but active only in females, would circumvent the need for sterilizing radiation, which can reduce fitness of released insects (Alphey and Bonsall 2018;Thomas et al 2000). Recent biotechnology efforts have been aimed at bioengineering transgenic plants or fungi that produce insect pheromones.…”
Section: Molecular Toolsmentioning
confidence: 99%
“…Our team has successfully established a CRISPR/Cas9‐based genome‐editing system and identified RNA polymerase type III (Pol‐III) promoters for expressing sgRNA in P. xylostella (Huang et al, ), though no case of gene drive strategy has been reported in P. xylostella . Nevertheless, the potential extinction of species (impacts on food webs or increased abundance of secondary pests in crops) and related ecologic risks (spread of gene drive systems into related taxa via hybridization) of global gene drive have raised widespread attention due to the concern of “virus‐like” spread of expression cassettes without limitation in wild populations (N. Alphey & Bonsall, ; Harvey‐Samuel et al, ). In addition, the resistance to sgRNA caused by mutation at the target site is also worthy of concern.…”
Section: Introductionmentioning
confidence: 99%